Photonic Diagnostics: Harnessing Optical Sensing for Non-Invasive Assessment of Coronary Obstruction - IR. Dr. Kazi Kutubuddin Sayyad Liyakat; Heena T Shaikh (International Journal of Optical Innovations & Research, 2026)
Cardiovascular diseases (CVDs) remain the leading cause of mortality globally, with coronary artery blockages primarily atherosclerosis representing a critical challenge. The gold standard for diagnosing coronary artery disease remains invasive coronary angiography, a procedure that, while precise, carries inherent patient risks, high costs, and logistical burdens. Optical sensors, leveraging the principles of light-tissue interaction, offer real-time, high-resolution insights into vascular health, paving the way for early detection of arterial stenoses and plaque vulnerability. This study investigates the integration of high-resolution optical sensor technology—specifically utilizing Photoplethysmography (PPG) and Near-Infrared Spectroscopy (NIRS)—as a non- invasive surrogate for detecting myocardial ischemia and arterial blockage. By analyzing the morphology of pulse wave propagation and the optical absorption spectra of hemoglobin within peripheral micro-vasculature, we developed a diagnostic framework capable of identifying hemodynamic irregularities indicative of coronary resistance. Our findings demonstrate that advanced signal processing, combined with multi-wavelength optical sensing, can distinguish between healthy hemodynamics and restricted coronary flow with an accuracy of 89.4%. The suggested solution prioritizes affordability and mobility, which makes it appropriate for ongoing remote monitoring and incorporation into wearable medical equipment. The study also emphasizes how data-driven insights from optical sensing technology may be used for individualized cardiovascular care and early risk assessment. This research posits that optical sensors offer a transformative potential for rapid, bedside triaging and long-term monitoring, effectively bridging the gap between passive wearable technology and clinical-grade diagnostic tools.
Keywords: Coronary Stenosis; Near-Infrared Spectroscopy (NIRS); Optical coherence tomography (OCT); Vascular Imaging; optical sensing; photoplethysmography (PPG)